The mediating role of innovation between corporate governance and organizational performance: Moderating role of innovative culture in Pakistan textile sector - Sajjad Nawaz Khan (Taylor & Francis Group, 2019)
The objective behind this research is to determine the influence of board size (BSZ), board independence (BID), board diversity (BDV), board meetings (BM), and a number of board committees (NBCM) on organizational performance with the use of innovation as mediating variable in Pakistan textile companies. Innovative culture uses as a moderating variable between innovation and organizational performance. Data were collected from top management and 550 questionnaires distributed among respondents. Only 407 questionnaires returned back and 384 questionnaires use for final analysis and remaining 23 questionnaires excluded due to missing values. PLS-SEM used for analysis purpose and data collected by using simple random sampling technique. Findings reveal that BSZ and BDV have a positive influence on organizational performance. Despite this, BID, NBCM, and BM have no influence on organizational performance. BSZ, BID, BDV, BM, and NBCM have a significant and positive influence on innovation. Innovation also significantly mediates between independent variables and organizational performance. Innovation has a positive influence on organizational performance. Moreover, innovative culture significantly moderates between innovation and organizational performance. Innovation and innovative culture is an important construct in determining organizational performance. It is beneficial for textile organizations to uses these two constructs in measuring organizational performance through corporate governance.